A very long engagement [videorecording (DVD)] = Un long dimanche de fiançailles - Jeunet, Jean-Pierre, 1953-; Tautou, Audrey, 1976-; Ulliel, Gaspard, 1984-2022; Pinon, Dominique, 1955-; Cotillard, Marion, 1975-; Japrisot, Sébastien, 1931-2003 (Warner Home Video, 2005)
Mathilde is waiting desperately for her fiance to return from the war. When bad news arrives she refuses to believe he is dead. Instead, she begins her own investigation into his infantry, hiring a private detective and piecing together his war stories.